Building a mutual relationship with nature: Experiences during early childhood - Fees, Bronwyn (Kansas State University, 2009)
Sustainability begins with an appreciation and wonderment of nature. Such dispositions develop through our earliest experiences with our environment, that is, during early childhood both at home and in early childhood education settings. Early childhood educators are well positioned to affect children’s dispositions toward and engagement with nature. Attitudes develop as an accumulation of experiences gained in every day situations over time. Best practices and professional teaching standards in early childhood education and science education require that pre-service teachers learn how to engage children to construct an understanding of ecology through careful observation of the natural world around them daily, to focus on the transformations that occur in the natural world (birth, growth, death, decay and decomposition) that occurs over time, and to appreciate the mutual dependency between the child and the natural world (Chaille & Britain, 2004; Kansas State Department of Education, 2007; National Association for the Education of Young Children, 2006; National Science Teachers Association, 2000). Teachers are directed to encourage a sense of wonder, not by manipulating nature, but through magnification of nature, recording (drawing, photograph…) nature and by capuslizing nature for a short time to observe and then release (Chaille & Britain, 2004). Empirical research suggests that children’s engagement with nature outside is also related to positive weight management, to attention in the classroom, and to positive mental health. Engaging children with nature affects positive well-being and dispositions that may encourage a positive attitude toward sustainability. Unfortunately, daily opportunities for engaging with nature are gradually becoming as endangered as nature itself as schools increasingly reduce or eliminate recess in favor of more instructional time. This presentation will examine curricular experiences designed by the master teachers at the KSU Ruth E. Hoeflin Early Childhood Education “Stone House” laboratory school to support young children’s appreciation, understanding, and engagement with nature as well as projects created by the college students in the early childhood education major, all guided by child development and professional standards.
Keywords: Childhood; Nature; Experiences; Relationship; Engagement; Educators